Not so strange bedfellows: new thoughts on King Philip I of Francia's marriage to Bertrada of Montfort. Issue 5 (19th October 2020) - Gabriele, Matthew
ABSTRACT: Too often, scholars have followed the analysis of reforming clerics in assessing the second marriage of King Philip I of Francia (1060–1108). Thus the union is termed 'adulterous' or 'bigamous', and the action a mark of decline upon his reign. But a sensitive reassessment of Philip I's actions in the early 1090s, positioned within the complicated politics of Maine, Anjou and Normandy allows us to see things a little differently. This essay therefore reconsiders the marriage of Philip I and Bertrada of Montfort in 1092 and the deft power politics that Philip played in order to increase his standing, particularly as he began to pivot and focus his attention to the south-west. In the end, this marriage expanded his power outside the Île-de-France and left the Capetians strengthened as they entered the twelfth century.